Water Relation and Growth of Simmondsia chinensis and Prosopis juliflora Seedlings at Nursery Stage - Burman, Uday; Bohra, M. D.; Harsh, L. N.; Tiwari, J. C. (Indian Forester, 2001)
Leaf water relation and growth of Simmondsia chinensis was compared with Prosopis juliflora a plant which had long ago achieved status of a ’weed’ and required replacement. Continuous monitoring of survival, shoot water potential, leaf transpiration, leaf turgiscence and dry matter accumulation at weekly intervals till the seedlings attained the ’transplantable’ growth revealed the superiority of S. chinensis. Coupled with high economic value, S. chinensis emerges out to be potential alternate to P. jUliflora in Indian arid tracts especially where limited irrigation is possible during the reproductive phase.